2022
DOI: 10.1186/s12889-022-13193-x
|View full text |Cite
|
Sign up to set email alerts
|

A tool for early estimation of influenza vaccination coverage in Spanish general population and healthcare workers in the 2018–19 season: the Gripómetro

Abstract: Asbtract Background Electronic vaccine registries are not yet widely established. There is a need to real-time monitor influenza vaccine coverage, which may raise awareness to risk groups and professionals, and eventually allow to adopt tailored measures during the vaccination campaign. To evaluate the utility of the “Gripómetro”, a demographic study designed to monitor national and regional influenza vaccine coverage on a weekly basis in Spain. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…Apart from clinical and care considerations, it is also important to consider the economic benefits of influenza vaccination. For the elderly, most published studies have found vaccination to be cost-effective, offering cost savings by reducing treatment costs that exceed the cost of vaccination [ 15 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from clinical and care considerations, it is also important to consider the economic benefits of influenza vaccination. For the elderly, most published studies have found vaccination to be cost-effective, offering cost savings by reducing treatment costs that exceed the cost of vaccination [ 15 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study of influenza‐related hospitalization costs in adults aged ≥ 65 years in Spain, vaccination reportedly reduced ICU admissions, rates of MV, and the degree of dependence on hospital services [ 43 ]. This is despite the influenza vaccination rate of 54.3% in this age group being short of the 75% goal recommended by the World Health Assembly [ 44 , 45 ]. Therefore, it is reasonable to suggest that newly available RSV vaccines could offer protection against the severity of RSV‐associated disease, thus reducing the burden on HRU.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Non-healthcare workers can benefit from vaccination through the prevention programs of their companies, but vaccination in work environment is very low, being below 11% in our case and in line with other studies published in Spain. 14 …”
Section: Discussionmentioning
confidence: 99%